How Important is Commercial Record Centre to the Information Industry in Malaysia? - Farah Azizzat Wan Nasrudin, Wan; Farik Mat Yatin, Saiful; Shafarin Shaari, Mohd; Nuruain Abu, Siti; Nurhidayah Wan Mohd Hatta, Wan; Hussin, Nurussobah; Zairul Masron, Mohd (International Journal of Engineering and Technology, 2018)
Commercial Records Centers (CRC), a potential business in records management services offer lot of opportunities for those who aware of the advantages. This is a good opportunity arise at the center of entrepreneur aspirations with economic and social conditions to create a new service, either in an existing market or a new one. Efficient administration of an organization and a good business are amongst the reflects of a great records management. Records management are one of the essentials instrument to smoothen administration process, providing data to plan and making decision, also a proof of transaction and existence.  Being an expert in business for any period of time, one will know that the archiving of business records’ is the most important thing. This article will discuss the potential of CRC, clarifying the strategy of marketing and the challenges face by this information industry in Malaysia